Implementation of Visual Learning Media to Improve Early Childhood Fine Motor in Tk PGRI Among Siwi, Adipuro Village, Kaliangkrik (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Fine   motor   skills   play   a   crucial   role   in   early   childhooddevelopment, involving  coordination  between  eyes  and  hands. This article explores the significance of early childhood education in nurturing these skills, particularly focusing on kindergarten-aged children. Drawing on various studies and educational theories, it emphasizes the importance of providing adequate stimulation and learning opportunities during the formative years of 0-6. The research highlights the need for innovative approaches in teaching methods, especially considering the tendency of young children to become easily bored. Utilizing the Asset-Based Community Development (ABCD) method, the study conducted  community service activities aimed at enhancing fine motor  skills in early childhood   within   a   specific   village.   Through   observation, interviews, and collaboration with teachers, the research identified weaknesses in fine motor skills among children and developed visual  learning  media  to   address  these  issues.  The  studyimplemented  various  activities  such  as  puzzles, coloring,  andcrafting, which proved to be engaging and effective in improving children's  motor  skills. Additionally, it  discusses the  theoretical framework of cognitive development, particularly Piaget's stages, emphasizing the role of play and hands-on experiences in facilitating learning. Ultimately, the article underscores the importance of utilizing available resources and integrating innovative learning media to create enjoyable and effective learning experiences for young children, thereby promoting their holistic development.